OXIDATIVE STRESS AND IMMUNE REACTIVITY: THE ROLE OF LIPID PEROXIDATION AND ANTIOXIDANT SYSTEMS IN STRESS ADAPTATION - Hamidova Saodat Khikmatovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This literature review analyzes the relationship between immunological reactivity, lipid peroxidation, and antioxidant defense mechanisms during stress conditions. Stress activates a complex cascade of neuroendocrine and biochemical reactions that disturb the balance between pro-oxidant and antioxidant systems. Excessive generation of reactive oxygen species (ROS) leads to lipid peroxidation, protein oxidation, and DNA damage, resulting in cellular dysfunction and immune imbalance. Numerous studies indicate that oxidative stress contributes to altered cytokine production, suppressed lymphocyte proliferation, and decreased phagocytic activity. The antioxidant system—comprising enzymes such as superoxide dismutase, catalase, and glutathione peroxidase—plays a compensatory role in neutralizing free radicals and maintaining redox homeostasis. The review highlights that prolonged or chronic stress depletes antioxidant reserves, weakens immune defense, and increases susceptibility to inflammatory and degenerative diseases. Understanding these interrelated processes provides insights for developing preventive and therapeutic approaches aimed at restoring oxidative and immune balance in stress-related disorders.